Phospholipid derived mediators and glomerulonephritis - E. N. Wardle (Mediators of Inflammation)
The contributions made by the various eicosanoids, PAF, the HETES and the lipoxins to the pathophysiology of glomerulonephritis is reviewed. A case can be made for clinical trials of PAF, leukotriene and thromboxane antagonists. Combined thromboxane synthetase and thromboxane receptor antagonism would seem to be the more efficacious approach for the various disease entities.